(3GdJfhjQ aj ehdO GdSQGL GdefjQs - (3CHh GdNWGH YeQ Hf GdMSf Hf Ydj Hf eMeO GdHdfSj GHf OMjI GdcdHj, GHf OMjI GdcdHj,J (B633 (3g` s ((3CHh GdeLO EHQGgje Hf GdMSf Hf Ydi GdEQHdi s)
(3ChdgG (B:s
(3hHYO agPG cJGH GdJfhjQ ai ehdO GdSQGL GdefjQ s
(3BNQgG (B:s
(3hGdMeO ddg MeO GdTGcQjfq s
(3Gdajde bSe Edi Qbejfs
(3HbjJg Qbe (B155 (3chjJs
(3HBNQgG eWGdYI eDQNI SfI (B1010 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs